Gambaran Tingkat Pengetahuan Mengenai Stroke pada Keluarga Pasien Pasca Stroke dengan Serangan Terakhir Kurang dari Satu Tahun: Literature Review - Septeana Tria Adin Adila; Fitria Handayani (Holistic Nursing and Health Science, 2020)
Introduction: Stroke patients rely heavily on family on decision-making for health actions should be done. The family members were found to have attitudes that are not right in doing in-home care for it is associated with knowledge of family low. On other side, the family knowledge level would lead in readiness of taking care of family members suffering from stroke with better. Based on the variation of knowledge level and influence, the researchers are interested to do literature review regarding the level of stroke knowledge on the patients families after the stroke last less than 1 year. Methods: The study aimed to review stroke knowledge level on the patients families after the stroke last attack less than 1 year. This study was a literature review conducted based on the issue, methodology, similarities and proposal advanced research. Search articles used EBSCO, google scholar, SINTA (Science and Technology Index), science direct, clinical key, and Scopus with the publication of the last 5-10 years. Results: The result showed that level of knowledge of post-stroke patients families with the last attacked less than a year from the ten articles that have been analyzed, 6 articles majority was still low with the range 63,8%-100% and 4 articles was high knowledge with the range 58%-74%. The majority low level of knowledge 3 articles was from India. Factors that affect the level of family knowledge about stroke were the education provision, education level and age.Conclusion: The stroke knowledge level in patients families post-stroke with the attacks last less than 1 year, the majority still in the low category so that expected health workers especially the nurses in giving health education on patients and families.